Improving the Design of Capacitive Micromachined Ultrasonic Transducers Aided with Sensitivity Analysis - Martowicz, A; Rosiek, M; Manka, M; Uhl, T (The International Journal of Multiphysics, 2011)
The paper presents the results of analysis performed to search for feasible design improvements for capacitive micromachined ultrasonic transducer. Carried out search has been aided with the sensitivity analysis and the application of Response Surface Method. The multiphysics approach has been taken into account in elaborated finite element model of one cell of described transducer in order to include significant physical phenomena present in modelled microdevice. The set of twelve input uncertain and design parameters consists of geometric, material and control properties. The amplitude of dynamic membrane deformation of the transducer has been chosen as studied parameter. The objective of performed study has been defined as the task of finding robust design configurations of the transducer, i.e. characterizing maximal value of deformation amplitude with its minimal variation.